Post-annealing of MAPbI3 perovskite films with methylamine for efficient perovskite solar cells. Issue 6 (12th August 2016) - Jiang, Yan; Juarez-Perez, Emilio J.; Ge, Qianqing; Wang, Shenghao; Leyden, Matthew R.; Ono, Luis K.; Raga, Sonia R.; Hu, Jinsong; Qi, Yabing
Abstract : Post-annealing of MAPbI3 perovskite films with methylamine improves both efficiency and stability of perovskite solar cells. Abstract : An organo-metal halide perovskite is a promising material for solar cell applications, but the polycrystalline nature of perovskites can cause thin films to be non-uniform with disconnected grains. These grain boundaries make the perovskite film vulnerable to the local chemical environment, or allow unwanted direct contact of the electron transporting layer and the hole transporting layer, increasing carrier recombination. We show that post-annealing with methylamine greatly reduces impurities at perovskite grain boundaries and promotes continuity between adjacent grains. When methylamine post-annealed perovskite films are compared to thermally or solvent-annealed films, the carrier lifetime is increased by 3 times. The recombination resistance for the planar perovskite solar cells with the methylamine post-annealing treatment is increased more than 10 times, and the efficiency is increased by 43.1% and 20.0% with respect to the thermally annealed and solvent-annealed perovskite solar cells, respectively. In addition, we show that methylamine post-annealed, meso-structured perovskite solar cells exhibited a power conversion efficiency of up to 18.4%, with significantly improved stability.